A Proteomics and Transcriptomics Investigation of the Venom from the Barychelid Spider Trittame loki (Brush-Foot Trapdoor) - Eivind A. B. Undheim; Kartik Sunagar; Volker Herzig; Laurence Kely; Dolyce H. W. Low; Timothy N. W. Jackson; Alun Jones; Nyoman D. Kurniawan; Glenn F. King; Syed Imran Ali; Agostinho Antunes; Tim Ruder; et al. (2013)
Although known for their potent venom and ability to prey upon both invertebrate and vertebrate species, the Barychelidae spider family has been entirely neglected by toxinologists. In striking contrast, the sister family Theraphosidae (commonly known as tarantulas), which last shared a most recent common ancestor with Barychelidae over 200 million years ago, has received much attention, accounting for 25% of all the described spider toxins while representing only 2% of all spider species. In this study, we evaluated for the first time the venom arsenal of a barychelid spider, Trittame loki, using transcriptomic, proteomic, and bioinformatic methods. The venom was revealed to be dominated by extremely diverse inhibitor cystine knot (ICK)/knottin peptides, accounting for 42 of the 46 full-length toxin precursors recovered in the transcriptomic sequencing. In addition to documenting differential rates of evolution adopted by different ICK/knottin toxin lineages, we discovered homologues with completely novel cysteine skeletal architecture. Moreover, acetylcholinesterase and neprilysin were revealed for the first time as part of the spider-venom arsenal and CAP (CRiSP/Allergen/PR-1) were identified for the first time in mygalomorph spider venoms. These results not only highlight the extent of venom diversification in this neglected ancient spider lineage, but also reinforce the idea that unique venomous lineages are rich pools of novel biomolecules that may have significant applied uses as therapeutics and/or insecticides.